A theoretical and experimental study of the temporal reduction in UV protection provided by a facial day cream. (31st August 2018) - Diffey, B. L.; O'Connor, C.; Marlow, I.; Bell, M.; O'Mahony, M. M.
Abstract: Objective: To investigate how the UV protection provided by a facial day cream reduces over the course of a day. Methods: We developed a theoretical model using a Monte Carlo random sampling approach to estimate the variation in local thickness, and hence local effective SPF, at several different sites over the face. The input variables, which are labelled SPF, average application thickness, homogeneity of the product on the skin and the ability of the product to bind to the skin, allow examination of how these different factors affect the delivered photoprotection. We compared the results of our modelling with experimental determination of the binding of an oil‐in‐water moisturizing day cream with a rated SPF of 15 at various times over the course of a day by means of UV photography and digital image analysis. Results: We demonstrated good agreement between our theoretical predictions of the temporal reduction in product thickness and the experimental observations. We used our modelling approach to show that a substantial reduction in lifetime UV burden on the face could be achieved by a daycare product delivering 3‐fold (or greater) protection over the face. Conclusion: Comparison with experimental data confirmed the robustness and validity of our model, which predicts that products intended for daily use need to be formulated carefully and applied uniformly, and to have a half‐life of binding to the skin of several hours. Products that bind less well to the skin, or are applied non‐uniformly, are likely to be providing inadequate protection with regards to influencing the rate of photoaging of the skin. Our data suggest that after a single, realistic application of a day cream rated SPF15, consumers' faces remain protected to at least an average of 5‐fold around the middle of the day, especially pertinent to indoor workers who are likely to be exposed to maximum UV levels as they venture outside during their lunch break. Abstract : We investigated how the UV protection provided by a facial day cream reduces over the course of a day by developing a computer model using a Monte Carlo random sampling approach. We demonstrated excellent agreement between our predictions and experimental observation of the binding of an oil‐in‐water moisturising day cream by means of UV photography and digital image analysis. We used our modelling approach to show that a substantial reduction in lifetime UV burden on the face could be achieved by a daycare product delivering 3‐fold (or greater) protection over the face.